The Indications for Catheter Ablation of Atrial Fibrillation - Stychynskyi, Oleksandr S.; Almiz, Pavlo O. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Since the introduction of catheter ablation of atrial fibrillation (AF), it developed from a specialized experimental procedure into a common treatment option to prevent recurrent AF. In recent years substantial improvement has been made in the equipment and techniques used in catheter ablation of AF. The volume of procedures expanded year after year. Naturally, this has been reflected on indications for catheter ablation. The aim. To study the changes in indications for catheter ablations of AF which has occurred during the last decade, according to European and American literature. Materials and methods. We reviewed four documents related to the management of AF: 2012 HRS/EHRA/ECAS expert consensus statement on catheter and surgical ablation ofatrial fibrillation; 2017 HRS/EHRA/ECAS/APHRS/SOLEACE expert consensus statement on catheter and surgical ablation of atrial fibrillation; 2016 ESC Guidelines for the management of atrial fibrillation developed in collaboration with EACTS; 2020 ESC Guidelines for the diagnosis and management of atrial fibrillation developed in collaboration with the European Association for Cardio-Thoracic Surgery (EACTS). Results. During the analyzed period there have been a lot of changes inindications for catheter ablation of AF. Recent years guidelines pointed out that a decision on AF catheter ablation should be based on the patient’s preferences. It is recommended to take into consideration the procedural risks andmajor risk factors of arrhythmia recurrence. All this should be discussed with patient. Today antiarrhythmic drugs still remain a first-line rhythm control therapy. Catheter ablation is recommended after drug therapy failure in patients with all clinical forms of AF. In AF patients with heart failure, when tachycardia-induced cardiomyopathy is highly probable, catheter ablation is recommended as a first-line therapy. Conclusion. Catheter ablation is effective in maintaining sinus rhythm in patients with paroxysmal and persistent AF. Its role as a method of rhythm control has increased during thelast decade.